2020
DOI: 10.3390/publications8010015
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ Publication Output: Self-Report Survey and Bibliometric Analysis

Abstract: The uncertainties around disease management and control measures have not only motivated clinicians to keep abreast of new evidence available in the scholarly literature, but also to be rigorously engaged in medical research, dissemination and knowledge transfer. We aimed to explore clinicians’ publication output from the Malaysian perspective. A self-report survey and bibliometric analysis was conducted. A total of 201/234 clinicians participated in the survey. Items consisted of demographics, researching hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The capability of a journal to disseminate to particular audiences (Solomon & Björk, 2012) included three dimensions: the audiences, channels, and effects of dissemination. Many studies found that audience characteristics, including the types (e.g., Tenopir et al, 2016), the number (e.g., Rowley et al, 2017), and the geographical region (e.g., Ganasegeran et al., 2020) of readers were important selection criteria. For example, a large‐scale survey divided readers into six categories and found that the academic audiences were the most important ones (Rowlands et al, 2004), which was also supported by other studies (Nicholas et al, 2017a; van Teijlingen & Hundley, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The capability of a journal to disseminate to particular audiences (Solomon & Björk, 2012) included three dimensions: the audiences, channels, and effects of dissemination. Many studies found that audience characteristics, including the types (e.g., Tenopir et al, 2016), the number (e.g., Rowley et al, 2017), and the geographical region (e.g., Ganasegeran et al., 2020) of readers were important selection criteria. For example, a large‐scale survey divided readers into six categories and found that the academic audiences were the most important ones (Rowlands et al, 2004), which was also supported by other studies (Nicholas et al, 2017a; van Teijlingen & Hundley, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Publications in English are frequently associated with utilitarian goals, such as gaining international recognition and reputation ( Burgess et al, 2014 ; Muresan and Pérez-Llantada, 2014 ; Rowley et al, 2020 ) and obtaining monetary rewards ( Lillis and Curry, 2010 ; Hanauer and Englander, 2011 ). This ties well with our findings, wherein journal indicators including journal reputation, audience, and journal impact factor seem to revolve around the perceived return value of scholarly publishing, as six interviewees mentioned: “the quality recognition of English papers in the evaluation and assessment is relatively high, which can provide more opportunities for salary increases.” Articles can be published in different languages to cater to various audience groups and characteristics, including audience type ( Tenopir et al, 2016 ), number ( Rowley et al, 2017 ), and geographic region ( Ganasegeran et al, 2020 ). Utilizing different languages and journals of varying prestige can result in precise dissemination to a specific audience, which can be rewarded with local prestige and recognition as well as better communication.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, publishable abstracts from our local researchers could have been submitted to discipline-specific conferences to garner attention from an audience in a relevant fraternity to maximize the impact of research findings. Secondly, a survey among Malaysian clinicians found that only 16.9% had published a paper throughout their clinical practice [28]. As the NCCR is organized by a research institute under the Malaysian MOH, a significant proportion of the presented abstracts were submitted by Malaysian clinicians and other healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to common observations that RCT abstracts have higher likelihoods of being published [3], only two out of the ten submitted RCT abstracts in our study were published. The reasons for non-publication were mainly due to time constraints and lesser prioritisations given to publish, which are commonly reported reasons among researchers who are working as healthcare professionals in the field [5,28,38]. Other reasons contributing to unpublished trials include the observation of undesirable results and protecting intellectual property rights [39,40].…”
Section: Discussionmentioning
confidence: 99%